IMPLEMENTASI PELATIHAN SERTA DAMPAKNYA TERHADAP KINERJA ISLAMI KARYAWAN BANK MANDIRI SYARIAH CABANG MALANG - Wilujeng, Sri (Fakultas Ekonomi, UIN Maliki Malang, 2017)
Abstract: The purpose of this study is to examines the influence of instructor/trainer, training materials,training methods of islamic performance. The research was conducted at PT Syaria Mandiri Bank branch ofMalang. There are 33 samples chosen at random sampling, and analysis used was multiple linear regressionmodels. Based on the research results, it can be concluded that the instructor, training materials, trainingmethods have a significant influence on islamic performance. The most dominant influence on the islamicperformance of employees is instructor. So it can be concluded that the variables comprising the instructor,training materials, training methods have an equally important role in improving islamic performance.